Effectiveness of government policies in response to the first COVID-19 outbreak. - Theologos Dergiades; Costas Milas; Elias Mossialos; Theodore Panagiotidis (PLOS Global Public Health, 2022)
This paper assesses the quantitative impact of government interventions on deaths related to the first COVID-19 outbreak. Using daily data for 32 countries and relying on the stringency of the conducted policies, we find that the greater the strength of government interventions at an early stage, the more effective these are in slowing down or reversing the growth rate of deaths. School closures have a significant impact on reducing the growth rate of deaths, which is less powerful compared to the case where a number of policy interventions are combined together. These results can be informative for governments in responding to future pandemics.